2019
DOI: 10.1051/e3sconf/201911101056
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-based Nanofluid Applications in Solar Thermal Energy

Abstract: Renewable energy sources such as solar, wind and geothermal are proposed as an alternative to fossil fuels whose excessive use causes global warming. The most popular one of the renewable energy sources is considered as solar energy due to the fact that required energy is provided by the sun entire year around the world. Solar energy systems convert the solar radiation to the useful heat or electricity. In order to achieve better performance in solar thermal systems many studies have been conducted. Some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Gupta et al [24] investigated on Al 2 O 3 water nanofluids and their flow rates on the efficiency of conventional solar collectors and enhanced efficiencies of more than 8% in comparison to pure water. Cobanoglu et al [25] studied on the utilization of nanofluids in solar thermal applications. They concluded that by the utilization of the carbon-based nanofluids enhanced the efficiency of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al [24] investigated on Al 2 O 3 water nanofluids and their flow rates on the efficiency of conventional solar collectors and enhanced efficiencies of more than 8% in comparison to pure water. Cobanoglu et al [25] studied on the utilization of nanofluids in solar thermal applications. They concluded that by the utilization of the carbon-based nanofluids enhanced the efficiency of the system.…”
Section: Introductionmentioning
confidence: 99%